Sosialiasi Faktor Resiko Perempuan Menjadi Korban Kekerasan Dalam Rumah Tangga Di Kota Sorong - Masniar Masniar; Lona Helti Nanlohy; Faried Desembardi; Nanik Purwanti; Uswatul Mardliyah; Lukman Rais; Siti Nurul Nikmatul Ula (ALKHIDMAH: Jurnal Pengabdian dan Kemitraan Masyarakat, 2023)
This research aims to determine the risk factors for women becoming victims of domestic violence. This research is qualitative in nature using a case study approach to analyze data based on quality and described using words so that language or explanation is obtained in the form of sentences that are systematic and easy to understand. The research results show that the background of women becoming victims of domestic violence includes family economic factors and family dysfunction, which causes violence against women. Cases of violence against women at the Sorong City Police Station this time have entered into a violence emergency status and there will be 33 cases in 2022. Long-term prevention of violence against women is through the use of Positive Deviance and psychosocial approaches for families in reducing the level of domestic violence.